Impaired activation of Notch-1 signaling hinders repair processes of bronchial epithelial cells exposed to cigarette smoke. (15th June 2020) - Di Sano, C.; D'Anna, C.; Ferraro, M.; Chiappara, G.; Sangiorgi, C.; Di Vincenzo, S.; Bertani, A.; Vitulo, P.; Bruno, A.; Dino, P.; Pace, E.
Highlights: Notch-1 intervenes in the reparative processes of the airway mucosa. cigarette smoke exposure limits Notch-1 signaling activation in bronchial epithelial cells. cigarette smoke exposure hinders repair processes in bronchial epithelial cells. Abstract: Notch-1 intervenes in the reparative processes of mucosa by controlling cell proliferation, differentiation and stem cell maintenance. Cigarette smoke alters airway epithelial homeostasis. The present study explored whether: Smokers showed altered Notch-1 expression; and whether in bronchial epithelial cells (16HBE): a) cigarette smoke extracts (CSE) altered the expression of Notch-1, of its ligand Jagged-1 (Jag-1) and the nuclear translocation of Notch-1; b) Notch-1 signaling activation as well as CSE modified Ki67, PCNA, p21, IL-33 expression, cell proliferation and repair processes. Notch-1 expression was assessed in the epithelium from large airway surgical samples from non-smoker and smoker subjects by immunohistochemistry.16HBE were cultured with/without CSE and Jag-1. A Notch-1 inhibitor (DAPT) was used as control. The expression of Notch-1, Jag-1, Ki67, PCNA, p21, IL-33 and cell proliferation (by CFSE) were all assessed by flow cytometry. Notch-1 nuclear expression was evaluated by immunofluorescence and western blot analysis. Repair processes were assessed by wound assay. Smokers had cytoplasmic but not nuclear Notch-1 expression. Although CSE increased Notch-1 expression, it counteracted Notch-1 signaling activation since it reduced Jag-1 expression and Notch-1 nuclear translocation. Notch-1 signaling activation by Jag-1 increased Ki67, PCNA and repair processes but reduced intracellular IL-33 and p21 expression without affecting cell proliferation. DAPT counteracted the effects of Notch-1 activation on PCNA and IL-33. CSE increased Ki67, PCNA, p21 and IL-33 expression but reduced cell proliferation and repair processes. In conclusion, cigarette smoke exposure, limiting Notch-1 signaling activation and hindering repair processes, amplifies injury processes in bronchial epithelial cells.